PERBANDINGAN ANATOMI KAYU RENGAS TEMBAGA (GLUTA RENGHAS L.) DENGAN RENGAS BURUNG (MELANORRHOEA WALLICHII HOOK. f) - Sri Rulliaty (Jurnal Penelitian Hasil Hutan, 1990)
Wood of renga1tembaga (Gluta renghas  L.) and ren,as IJurung(Melanorrhoea  wallicbii Hook.(.) ltaue many common limilaritia   in the anatonJicalfeatures.Some of the differencel are in the grou feature of wood. Anatomical 1tudy 1hows that the frequency of Pora  and raya  dimenaion (width and height) of  Melanorrhoea   wallichii  Hook.f.  are significantly different  compared with those of  Gluta  renghas  L.